Structural safety assessment for 100-seater totally enclosed lifeboat. (1st January 2014) - Choi, Joo-Hyoung; Choi, Shin-Hyeong
The 100-seater totally enclosed lifeboat is an essential safety equipment to escape in offshore structure. Therefore, structured safety assessment for lifeboat must be made essentially to operate normally in case of emergency. In this paper, the structural strength analysis is performed for a variety of conditions when the 100-seater totally enclosed lifeboat is installed on the hook of davits. The 100-seater totally enclosed lifeboat study has been performed using the software ANSYS ver. 13.0, FE analysis programme. By using the software ANSYS programme in the shipbuilding industry, it will contribute to technology development and productivity of the 100-seater totally enclosed lifeboat. Also through the simulation and analysis code, it will contribute greatly to the development of IT.